Introductory Essay on an Understanding of the Triple-frontier Area: Preliminary Turkologic Research - Moačanin, Nenad (Array, 1998)
Ottoman sources dealing with the Vlach population living in the broader area of the Triple border in Croatia and Bosnia show that all changes in taxation, broadening or lessening of alleged privileges etc. did not alter the fundamental characteristic of that people, that is their relatively uniform appear from the standpoint of culturology.